KEDISIPLINAN BELAJAR SISWA DITINJAU DARI PERAN ORANG TUA DALAM MENGONTROL PENGGUNAAN GADGET - Dewa Ayu Widiyanti; I Gusti Agung Ayu Wulandari; I Wayan Wiarta (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The development of technology makes gadget users not only come from adults but also children, who utilize gadgets in their daily activities. However, the use of gadgets among children without parental supervision has a negative influence on children, thus impacting their discipline, especially on children's learning discipline at school and home. This study aims to determine the discipline of student learning due to the use of gadgets in daily life and the role of parents in controlling the use of gadgets in grade IV students of Elementary School Cluster III, Susut District, Bangli Regency. This research uses a qualitative approach with a descriptive type of research. The subjects in this study were as many as ten parents and grade IV elementary school students in Elementary School Cluster III, Susut District, Bangli Regency. Data collection uses non-test methods through questionnaires, interviews, observations, and documentation. Data analysis techniques use descriptive qualitative and statistical analysis techniques. The results of data analysis in this study showed a percentage of 38.58% in student learning disciplines with low categories. Meanwhile, the results of data analysis on the role of parents in controlling the use of gadgets showed a percentage of 39.37% where these results were categorized as low category.